Intravascular ultrasound use for stent optimization during percutaneous coronary intervention in a toddler with post-surgical stenosis after coronary reimplantation for ALCAPA. Issue 2 (August 2020) - Sang, Charlie Joseph; Prejean, Shane; Von Mering, Gregory; Ahmed, Mustafa; Law, Mark A.
Abstract: Percutaneous coronary intervention (PCI) is an uncommon procedure in the pediatric population, and the use of intravascular ultrasound (IVUS) to guide stent optimization in this setting is not well described. We present a case of a 22-month old female who developed left main coronary stenosis following surgical correction of anomalous left coronary artery from the pulmonary artery (ALCAPA). PCI was pursued, and with the use of IVUS, stent placement was determined to be optimal. Given the limited data on the use of IVUS in PCI for children, we discuss the unique applications of IVUS, drug-eluting stents, and future clinical concerns following management of post-surgical stenosis following ALCAPA repair. 〈Learning objective: Percutaneous coronary intervention is a rare procedure in the pediatric population, and the use of intravascular ultrasound to optimize stent placement is not well described in this setting. Intravascular ultrasound may allow for more precise stent placement and may be useful during acute and long-term management of pediatric patients undergoing percutaneous coronary intervention.〉